THE ROLE OF BANKS IN THE FORMATION OF FAVORABLE INVESTMENT CONDITIONS IN THE REPUBLIC OF UZBEKISTAN - Abdullaev Muzaffar Abdujabbarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
by actively participating in the creation of an effective model of the market economy, which reflects the peculiarity of the national economy of Uzbekistan, commercial banks pay great attention to the formation of the local market of securities.